Social Media Addiction as Predictors of Sleep Quality: Lens from University of Ibadan Athletes: Social Media Addiction as Predictors of Sleep Quality: Lens from University of Ibadan Athletes - Balogun, Olaitan Johnson; Quadri, Ganiyu Oluwaseyi; Ukpere, Wilfred Isioma (Journal of Economic Development, Environment and People, 2026)
The‍‌‍‍‌‍‌‍‍‌ research aimed at investigating the extent to which social media addiction (SMA) could predict sleep quality among athletes (SQAA) of the University of Ibadan. The study employed a descriptive correlational research design and had as its population 154 athletes from the institution. The census sampling technique was used to ensure that all athletes were part of the research. The research was guided by three questions. The theoretical basis of the research was the Self-Regulation Model (SRM) supplemented by the Technology Acceptance Model (TAM). Data was obtained using a questionnaire made by the researchers themselves, and analysis was done using descriptive statistics. The study found that the major determinants of SQAA among the variables studied were time spent on social media (SM) (38.3%), stress (24.0%), pain (21.3%), and physical activity (12.3%). Furthermore, the results indicated that SMA caused a serious change in sleep quality (SQ), where the major effects were identified as fatigue (31.8%), poor performance (29.2%), insomnia (29.2%), and reduced sleep duration (29.2%). The most popular platforms used by athletes that affected their sleep were WhatsApp (37.7%), Instagram (29.9%), and X/Twitter (15.6%). The research concluded that SM overuse among students significantly deteriorates SQAA, leading to the obstruction of their sports performance. Consequently, it is suggested that athletes limit their social media usage, especially at night, carry out digital wellness initiatives, and set up co-support systems with the help of coaches and sports ‍‌‍‍‌‍‌‍‍‌psychologists.